Gendered associations of situational and dispositional factors with exclusion from social relations and loneliness in older age - Georgios Pavlidis; Georgios Pavlidis (Frontiers in Public Health)
BackgroundStates of exclusion from social relations (ESR) refers to severe social isolation in older age that is not always typified by increased loneliness. Relevant deficiencies in the social network of older persons may be gendered and associated with personality and socioeconomic barriers, with direct implications for older persons’ welfare. Although the contribution of personality traits and socioeconomic barriers in shaping ESR states in older age are often debated, empirical evidence that addresses their unique contribution is limited. Therefore, the aim of this study was to examine the gender-stratified associations of situational (e.g., marital status, socioeconomic conditions) and dispositional factors (i.e., personality traits) with ESR states and loneliness in older age.MethodsA cross-sectional and gender-stratified secondary analysis of a sample (N = 36,814) from the Survey on Health, Aging, and Retirement in Europe was conducted using logistic regression models.ResultsThe probability of ESR was higher among older men. Certain situational factors (e.g., widowed, never married) significantly increased the probabilities of ESR for both genders, while other (e.g., divorce) had a gender-specific significance. Less extraversion among older women and less conscientiousness among older men was associated with an increased probability of ESR in later life. Within ESR states, older men living alone and older women who are less extraverted were more at-risk of loneliness.ConclusionSituational factors are more predictive of ESR states than personality traits, yet a gendered perspective is needed when assessing the risk factors of ESR and loneliness in later life.